Role of Hysteroscopy on Infertility: The Eternal Dilemma - Marianna Gulisano; Ferdinando Antonio Gulino; Giosuè Giordano Incognito; Monia Cimino; Valentina Dilisi; Alessandra Di Stefano; Valentina D’Urso; Francesco Cannone; Francesco Giuseppe Martire; Marco Palumbo (Clinical and Experimental Obstetrics & Gynecology)
Hysteroscopy is the gold standard tool for endoscopic visualization of the uterine cavity and it assesses a simultaneous detection and treatment of intracavitary anomalies with greater accuracy than other methods. The most common uterine abnormalities, including endometrial polyps, submucosal myomas, uterine septum and intrauterine adhesions, are common in infertile women. It is object of debate whether diagnostic and/or operative hysteroscopy should be considered in the basic work-up of infertile couples.